Odpowiedzi

2010-03-05T20:39:19+01:00
Y -3y= y(1-3)
15a + 12b= 3(5a+4b)
24x- 16y= 8(3x-2y)
12a - 8b= 4(3a-2b)
10n - 15m=5(2n-3m)

4x-8y-4z= 4(x-2y-1)
6a-9b+12y= 3(2a-3b+4y)
12a+8m-20= 4(3a+2m-5)
5a-15b+20c= 5(a-3b+4c)
30x+18y-6= 6(5x+3y-1)
36a+12b-6= 6(6a+2b-1)
63m+54n-9= 9(7m+6n-1)
3,5a+0,7b-14=7(0,5a+0,1b-2)
2010-03-05T21:00:14+01:00
1. Zamień sumę na iloczyn
y -3y=y*(1-3)=
15a + 12b=3(5a+4b)
24x- 16y=4(6x-4y)
12a - 8b=4(3a-2b)
10n - 15m=5(2n-3m)
3. Wyłącz wspólny czynnik przed nawias
4x-8y--4z=4(x-2y-z)
6a-9b+12y=3(2a-3b+4y)
12a+8m-20=4(3a+2m-5)
5a-15b+20c=5(a-3b+4c)
30x+18y-6=6(5x+3y-1)
36a+12b-6=6(6a+2b-1)
63m+54n-9=9(7m+6n-1)
3,5a+0,7b-14= 7(0,5a+0,1b-2)
2010-03-05T21:35:02+01:00
Y -3y= y(1-3)
15a + 12b= 3(5a+4b)
24x- 16y= 8(3x-2y)
12a - 8b= 4(3a-2b)
10n - 15m=5(2n-3m)

4x-8y-4z= 4(x-2y-z)
6a-9b+12y= 3(2a-3b+4y)
12a+8m-20= 4(3a+2m-5)
5a-15b+20c= 5(a-3b+4c)
30x+18y-6= 6(5x+3y-1)
36a+12b-6= 6(6a+2b-1)
63m+54n-9= 9(7m+6n-1)
3,5a+0,7b-14=0,7(5a+b-20)


Naa 100% dobrze,bo na lekcji z nauczycielem to rozwiązywałam :p